(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Fungal infections in seeds pose significant challenges to agricultural productivity and food security. The present study investigates the viability and occurrence of fungal infections in Brinjal (Solanum melongena), Coriander (Coriandrum sativum), and Cowpea (Vigna unguiculata) seeds by agar plate method. The study aims to assess the prevalence and severity of fungal pathogens and identify potential risk factors. The research utilized laboratory analysis and microscopy to identify fungal species and evaluate seed viability. Results highlight the impact of fungal infections on seed quality and provide valuable insights for sustainable seed management practices.